Optical coherence tomography assessment of a complex bifurcation lesion treated with double kissing Crush technique: A case report. Issue 1 (January 2017) - Cai, Jin-Zan; Zhang, Yao-Jun; Xu, Tian; Zhu, Yong-Xiang; Mao, Chen-Yu; Bourantas, Christos V.; Crake, Tom; Chen, Shao-Liang
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The DEFINITION (Impact of the complexity of bifurcation lesions treated with drug-eluting stents) study has provided a novel classification to evaluate the complexity of coronary bifurcation lesion according to coronary angiography, but angiographic imaging due to its low resolution and inherited limitation may result in an inaccurate adjudication. We used optical coherence tomography (OCT) to further evaluate the coronary characteristics in a patient with "simple" bifurcation lesion which was classified by the DEFINITION criteria. However, a "complex" bifurcation lesion was defined and confirmed according to the OCT results. A double kissing Crush stenting approach was adopted to treat this "complex" case finally. The immediate and long-term angiographic and OCT results were excellent. OCT may be useful imaging modality to classify complexity of coronary bifurcation lesion and subsequently guide its treatment strategy.